USULAN KEBIJAKAN PERSEDIAAN PRODUK PADA PT. XZY DENGAN METODE CONTINUOUS REVIEW DAN PERIODIC REVIEW UNTUK MINIMASI OVERSTOCK - Munawaroh, Diela Qoriatul; Damayanti, Dida Diyah; Suryadhini, Pratya Poeri (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This research aims to determine inventory policy planning using the Continuous Review and Periodic Review method to Minimize Overstock. The research methods used in this research are the Continuous Review and Periodic Review methods to minimize overstock. Data collection through observation, documentation and interviews. This research classifies products using ABC analysis. The results of the ABC analysis classification, namely 3 types of products including category A, 3 types of products including category B, and 2 types of products including category C. Based on the results of the ABC analysis classification, categories A and B are calculated using the continuous review method (s, S) and category C will be calculated using the periodic review method (R, s, S). Based on the results of data processing, the amount of proposed inventory produced has decreased by around 39% and the cost of proposed inventory by around 90%. Therefore, it can be concluded that the proposed inventory policy using the continuous review (s, S) and periodic review (R, s, S) methods is able to minimize overstock that occurs at PT. XYZ.